The Development of Salt Resources in Pakistan under the Perspective of the China-Pakistan Economic Corridor - Yang, Yong; Wang, Shangli (Pacific International Journal, 2022)
The salt play an important role in daily life and industry. There are large reserves of high - quality salt deposits in Pakistan. But Pakistani salt resources have a smaller share in international salt trade. The paper analyses the current situation in terms of the development of salt resources in Pakistan through SWOT analysis under the perspective of the China-Pakistan Economic Corridor. On this basis, the paper puts forward some countermeasures and suggestions for developing salt resources in Pakistan, such as increasing salt export, developing the health and wellness tourism with salt as the theme, establishing salt chemical industry chain based on strengthening Sino-Pakistan production capacity cooperation. These measures will help to further alleviate Pakistan’s balance of payments.